Investigating the Perception of Algerian Secondary EFL Teachers towards Critical Pedagogy - Berriche, Abdelali; Merrouche, Sarah (جامعة العربي بن مهيدي - أم البواقي, 2021)
لقد ساهم تطبيق مبادئ البيداغوجيا النقدية في مجال تعليم وتعلم اللغة الإنجليزية كلغة أجنبية في العقود القليلة الماضية في ظهور وجهات نظر نقدية تجاه دور المعلمين. على الرغم من الانتشار السريع للغة الإنجليزية في الجزائر وأهمية القضايا التي تعالجها البيداغوجيا النقدية في تعليم وتعلم اللغة الإنجليزية كلغة أجنبية، فقد أجريت دراسات قليلة لاستطلاع آراء مدرسي اللغة الإنجليزية كلغة أجنبية حول قاعدتها النظرية وتطبيقها داخل الفصل الدراسي. لذلك هدفت الدراسة الحالية إلى دراسة موقف مدرسي اللغة الإنجليزية كلغة أجنبية حيال مبادئ البيداغوجيا النقدية وكذا تطبيقها في أنشطة ما قبل وأثناء الصف. أجري الاستبيان على ستين مدرسا للغة الإنجليزية في ولاية أم البواقي، الجزائر. كشفت النتائج الرئيسية أن هناك وعيا متدنيا بالبيداغوجيا النقدية بين مدرسي اللغة الإنجليزية نظرا للهيكل المؤسسي الذي يفضل البيداغوجيا السائدة. تشير هذه النتائج إلى الحاجة الماسة لاستكشاف سبل أخرى لرفع وعي المعلمين بالبيداغوجيا النقدية.
The application of the principles of Critical Pedagogy to the field of EFL teaching and learning in the last few decades has contributed to the emergence of critical perspectives toward the role of teachers. Despite the rapid spread of English in Algeria and the relevance of the issues addressed by Critical Pedagogy in EFL teaching and learning, few studies have been conducted to survey Algerian EFL teachers' Views towards its theoretical base, and its application inside the classroom. The present study, therefore, aimed at investigating the Algerian EFL teachers’ attitude as well as the application of Critical Pedagogy principles in pre-during and after-class activities. The developed questionnaire was administered to sixty teachers of English at the Wilaya (district) of Oum El Bouaghi, Algeria. The main findings revealed that there was very little awareness of Critical Pedagogy among ELT teachers due to institutional structure that favors mainstream pedagogy. These findings point to a dire need for exploring other venues for raising teachers’ awareness of critical pedagogy.
Keywords: معلمو اللغة الإنجليزية -- الكفايات التدريسية -- التأهيل المهني -- التعليم الثانوي -- الجزائر